La Sociedad Anónima Abierta: algunas ideas para la reforma de su tratamiento legislativo - Payet Puccio, José Antonio (2017)
In this paper, the author focuses on the study of the legal institution of the Open Stock Corporation, analyzing the way how it has been treated in our legislation over time. Furthermore, he analyzes its current regulation in the General Law of Corporations, the Securities Market Law and some isolated legal provisions. Finally, he provides some ideas for the necessary reform of this institution.